Energy futures modelling for African countries: LEAP model application - Nadia S. Ouedraogo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This study develops a scenario-based model to assess the current and future trends in energy demand in Africa and associated greenhouse gas emissions. Future energy demand is forecast on the basis of socio-economic variables such as gross domestic product, income per capita, population, and urbanization. The Long-range Energy Alternative Planning model is applied to analyse and project energy demand and the related emissions under alternative strategies for the period 2010-2040. Two main policy implications can be derived from the results of this study. First, it is essential for Africa to promote energy conservation policies that will improve energy efficiency and address issues related to energy shortages, energy poverty, and energy security. Second, policies that favour cleaner energies over other sources are required as early as possible to displace fossil fuel usage and to support sustainable economic development.
Keywords: Q47; Q41; Q42; Q43; Q48; Q50; 330; energy forecasting; energy efficiency; renewables; sustainable energy for all; carbon emission intensity; climate change